The Mediating Role of Return on Equity in The Influence of Intellectual Capital on The Islamic Social Responsibility - Chandra Zaki Maulana; Fernando Africano; Lidia Desiana; Yuyus Suryana; Dwi Kartini; Erie Febrian (Journal of International Conference Proceedings (JICP), 2018)
This study aimed to find empirical evidence concerning the role of Return on Equity (ROE) as the mediation variable over the influence of Intellectual Capital (IC) on the Islamic Social Responsibility (ISR). IC was measured by using all intangible assets of a corporate organization including the innovation capacity, financial and human resources within a system intended to create Value Added Service Intellectual Capital (VAIC), which is an intellectual material which has been formulated and captured in order to create wealth, resulting in a highly valued asset. As for ISR is measured by utilizing an Index consisted of a compilation of CSR standard items determined by Accounting and Auditing Organization for Islamic Financial Institution (AAOIFI) and furtherly developed by researchers concerning CSR items which should be disclosed by an Islamic entity. The ISR Index is expected to be the starting point in terms of CSR disclosure which is compliance to the Islamic perspective. Population in this research is Sharia Commercial Banks (SCB) in Indonesia in which regularly issued annual report for a period of four years (2012 to 2016). Method used to draw sample is purposive sampling with certain criterions. The total sample is 10 SCBs. Data collected via website of Indonesia Financial Service Authority (OJK) and the financial report by each SCB which consisted of annual report and company financial statements. Analysis technique used is path analysis and data is being processed by IBM SPSS program. Data were previously tested and have met all of classic assumptions. The results showed that IC has a positive and significant influence on ISR. ROE has a negative and significant influence on ISR. IC is positively and significantly influencing ROE, and ROE is able to mediate the influence of IC on the ISR. Keywords: Return on Equity, Intellectual Capital, Islamic Social Responsibility